ASSESSMENT OF THE TREND OF ECONOMIC SECURITY IN THE REGIONS (Marketing Journal, 2025)
This article analyzes the dynamic changes in economic security indicators in the regions of Uzbekistan for the period 2010 –2014 and 2020 –2024 on a scientific basis. During the study, the theoretical foundations of national and regional economic security, the system of threats and factors determining interregional development differences were studied in depth. The economic potential of the regions, the efficiency 71 of resource use, investment activity, the level of industrialization and the impact of demographic burden on changes were assessed based on statistical data. The results of the analysis showed that economic growth was unevenly distributed across regions, economic security was significantly strengthened in some regions, and decreased in others. The article develops scientifically based proposals aimed at reducing interregional disparities, strengthening economic security and ensuring sustainable development.
Keywords: economic security; regional development; interregional disparities; investment potential; economic diversification; regional governance